113 - VIOLENCE AGAINST WOMEN IN THE SERTÃO OF PARAÍBA: A DOCUMENTARY RESEARCH (Fiep Bulletin - online, 2011)
Brazil stands out from other countries when it comes to violence against women because of the consequences to the women's health and the difficulty in monitoring the cases, due to their private character. This study aims to draw a profile of women who suffer violence, taking into consideration their socio-demographic profile, the main forms of aggression and the relationship victim-offender. This is a research of documentary, exploratory, retrospective and descriptive character, with a quantitative approach. It was developed in the files of the Police Office Specialized in Women Assistance. The sample consisted of 60 police reports (BO) and, for the collect of data, a script guided the BOs examination. Data were quantitatively analyzed and put into graphics and tables, according to the pertinent literature. After data analysis, we found that the percentage distribution of women victims of violence corresponds to the age group between 20 and 40 years old. Regarding their marital status, most of these women are married. The form of violence that appears the most is the domestic violence, with a percentage of 29%. The main aggressors are the victims' husbands or ex-husbands (54%) and the place in which the cases happen most is the house (62%). This study, therefore, reveals that the violence against women is a noteworthy and worrying problem of public health that increases by the hour, making the family environment become a dangerous place for many women, causing mental and physic problems, what makes it necessary to pay attention to efficient public policies, as well as an appropriate and specific care from health professionals towards this portion of the population.
Keywords: Gender; Public Policies; Violence against women